Intra-Specific Divergence in Moth Bean for Grain Yield and its Components - Jindal, S K (Annals of Arid Zone, 2016)
Genetic divergence, as measured by Mahalanobis D2 statistics was studied in 22 diverse genotypes of moth bean [Vigna aconitifolia (Jacq ) Marechal).The genotypes were grouped into seven clusters. Geographic diversity did not seem to have a direct association with genetic diversity. Use of IPCMO WI5, IPCMO 569, IPCMO 939, IPCMO 911 and Jadia in crossing programme is advocated.